Ethnic Disparities in School‐Based Behavioral Health Service Use for Children With Psychiatric Disorders. (4th December 2016) - Locke, Jill; Kang‐Yi, Christina D.; Pellecchia, Melanie; Marcus, Steven; Hadley, Trevor; Mandell, David S.
ABSTRACT: BACKGROUND: We examined racial/ethnic disparities in school‐based behavioral health service use for children with psychiatric disorders. METHODS: Medicaid claims data were used to compare the behavioral healthcare service use of 23, 601 children aged 5‐17 years by psychiatric disorder (autism, attention deficit hyperactivity disorder [ADHD], conduct/oppositional defiant disorder, and "other") and by race/ethnicity (African‐American, Hispanic, white, and other). Logistic and generalized linear regression analyses were used. RESULTS: Differences in service use by racial/ethnic group were identified within and across diagnostic groups, both for in‐school service use and out‐of‐school service use. For all disorders, Hispanic children had significantly lower use of in‐school services than white children. Among children with ADHD, African‐American children were less likely to receive in‐school services than white children; however, there were no differences in adjusted annual mean Medicaid expenditures for in‐school services by race/ethnicity or psychiatric disorders. Statistically significant differences by race/ethnicity were found for out‐of‐school service use for children with ADHD and other psychiatric disorders. There were significant differences by race/ethnicity in out‐of‐school service use for each diagnostic group. CONCLUSIONS: Differences in the use of school‐based behavioral health services by racial and ethnic groups suggest the need for culturally appropriate outreach and tailoring of services to improve service utilization.